The Old Testament library : Ruth : a commentary - Nielsen, Kirsten, 1943- (Louisville, Westminster John Knox Press, 1997)
The book of Ruth is one of the Bible's most enduring and beloved stories. At first glance, the story appears to be a simple tale of hardship and good fortune, but a close reading of the short book yields wonderful new insights. Kirsten Nielsen's comments on the book of Ruth paint a rich and subtle portrait of the characters involved in the story. She carefully traces the many connections between this biblical book and the wider context of other biblical passages, including earlier stories such as the story of Judah and Tamar, and later adaptations such as the Targum to Ruth. Nielsen provides the reader an entry to this nuanced intertextual world.
Includes bibliographical references (pages xi-xiv) and indexes.
Keywords: Bible. -- Commentaries; Commentaries